PSYCHOLOGICAL CONSEQUENCES OF BULLYING FOR THE PERSONALITY OF A TEENAGER AND HIS SOCIALIZATION - Amirova Luiza Maratovna (Bright Mind Publishing, 2025)
The article presents the views on the psychological consequences of bullying for the personality of a teenager and his socialization, the results of scientific research, the results of analysis in schools, and the cases of harm to each other in adolescents.
Keywords: Bullying, life, school, social, consciousness, state, aggression, anger, violence, emotion.